Effect of Proton Irradiation Followed by Hindlimb Unloading on Bone in Mature Mice: A Model of Long-Duration Spaceflight - Lloyd, Shane A. (2012)
Bone loss associated with microgravity unloading is well documented; however, the effects of spaceflight-relevant types and doses of radiation on the skeletal system are not well defined. In addition, the combined effect of unloading and radiation has not received much attention. In the present study, we investigated the effect of proton irradiation followed by mechanical unloading via hindlimb suspension (HLS) in mice. Sixteen-week-old female C57BL/6 mice were either exposed to 1 Gy of protons or a sham irradiation procedure (n=30/group). One day later, half of the mice in each group were subjected to four weeks of HLS or normal loading conditions. Radiation treatment alone (IRR) resulted in approximately 20% loss of trabecular bone volume fraction (BV/TV) in the tibia and femur, with no effect in the cortical bone compartment. Conversely, unloading induced substantially greater loss of both trabecular bone (60–70% loss of BV/TV) and cortical bone (approximately 20% loss of cortical bone volume) in both the tibia and femur, with corresponding decreases in cortical bone strength. Histological analyses and serum chemistry data demonstrated increased levels of osteoclast-mediated bone resorption in unloaded mice, but not IRR. HLS+IRR mice generally experienced greater loss of trabecular bone volume fraction, connectivity density, and trabecular number than either unloading or irradiation alone. Although the duration of unloading may have masked certain effects, the skeletal response to irradiation and unloading appears to be additive for certain parameters. Appropriate modeling of the environmental challenges of long duration spaceflight will allow for a better understanding of the underlying mechanisms mediating spaceflight-associated bone loss and for the development of effective countermeasures.